2020
DOI: 10.1177/8755122520934726
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ceftazidime-Avibactam, Meropenem-Vaborbactam, and Imipenem/Cilastatin-Relebactam to Target Klebsiella pneumoniae Carbapenemase-Producing Enterobacterales

Abstract: Objective: To provide a review of 3 novel antimicrobial agents—ceftazidime-avibactam, meropenem-vaborbactam, and imipenem/cilastatin-relebactam—regarding treatment of Klebsiella pneumoniae carbapenemase-producing Enterobacterales (KPC). Data Sources: A literature search of PubMed and OVID (MEDLINE) was performed up to March 2020 using the following search terms: Vabomere, meropenem-vaborbactam, vaborbactam, RPX7009, Klebsiella pneumoniae carbapenemase, KPC, carbapenem-resistant Enterobacteriaceae, CRE, relebac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…choosing these new agents. For instance, IMI/REL along with ceftazidime/avibactam and meropenem/vaborbactam are effective against the resistant mechanisms of ESBL, AmpC, and KPC [33,34]; and ceftazidime/ avibactam and IMI/REL both have good activity against multidrug resistant P. aeruginosa [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…choosing these new agents. For instance, IMI/REL along with ceftazidime/avibactam and meropenem/vaborbactam are effective against the resistant mechanisms of ESBL, AmpC, and KPC [33,34]; and ceftazidime/ avibactam and IMI/REL both have good activity against multidrug resistant P. aeruginosa [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, new combinations of antibiotics in conjunction with β-lactamase inhibitors e.g., meropenem with vaborbactam or imipenem with relebactam, offer hope in treating resistant strains [ 42 , 43 , 44 , 45 , 46 , 47 ]. Additionally, some new agents are developed to cope with such infections [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of this report, the European Medicines Agency (EMA) has approved several new broad-spectrum antibiotics. Two of them are new combinations of carbapenems with non-β-lactam inhibitors of β-lactamases (also active against carbapenemases), belonging to two new groups of inhibitors: diazabicyclooctane (relebactam, associated with imipenem) and boron (vaborbactam, associated with meropenem) [ 47 ]. The third new drug is a siderophore cephalosporin (cefiderocol) with an innovative mechanism of penetration into the bacterial cell [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Recently, it has been reported that three novel β-lactam (BL)/BLI combinations would be effective for the treatment of KPC-producing Enterobacterales ; ceftazidime-avibactam (CAZ/AVI), meropenem-vaborbactam, and imipenem/cilastatin-relebactam. 5 Not surprisingly, the emergence of CAZ/AVI resistance has been reported since the introduction of CAZ/AVI and 2–8% of K. pneumoniae harboring KPC (KPC-KP) in the United States (US) and Europe are currently CAZ/AVI-resistant. 6 7 8 9 10 CAZ/AVI resistant KPC strains were mainly identified in the US, Italy and Greece, countries where prevalence of KPC-producing K. pneumoniae is high.…”
Section: Introductionmentioning
confidence: 99%